2016
DOI: 10.15244/pjoes/60160
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immobilization of Polycyclic Aromatic Hydrocarbons in Contaminated Soil Using Forest Wood-Derived Biochar and Activated Carbon under Saturated Conditions, and the Importance of Biochar Particle Size

Abstract: Leaching behavior of organic contaminants such as polycyclic aromatic hydrocarbons (PAHs) can be altered in the presence of organic amendments through enhanced sorption of PAHs to the amended soil. The aim of the present study was to investigate the influence of biochar in two forms (i.e., crushed and pulverized), and granular activated carbon on immobilization and leaching behavior of selected PAHs from contaminated soil into water using the column leaching test. The influence of biochar particle size on leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…And soil translocation, erosion, leaching, and other hydrologic/climatic-related processes of a region are likely to act to mobilize both pyOM and non-pyOM in similar ways (Hilscher and Knicker, 2011;Jien and Wang, 2013), though not necessarily to equal extents (Rumpel et al, 2009). Finally, it has been suggested that pyC mobilization may occur via association with other OM in dissolved or perhaps colloidal (Zand and Grathwohl, 2016;Kumari et al, 2017) form, but the controlling mechanisms are still unknown (Wagner et al, 2017).…”
Section: Methodology/conceptual Issuesmentioning
confidence: 99%
“…And soil translocation, erosion, leaching, and other hydrologic/climatic-related processes of a region are likely to act to mobilize both pyOM and non-pyOM in similar ways (Hilscher and Knicker, 2011;Jien and Wang, 2013), though not necessarily to equal extents (Rumpel et al, 2009). Finally, it has been suggested that pyC mobilization may occur via association with other OM in dissolved or perhaps colloidal (Zand and Grathwohl, 2016;Kumari et al, 2017) form, but the controlling mechanisms are still unknown (Wagner et al, 2017).…”
Section: Methodology/conceptual Issuesmentioning
confidence: 99%
“…Biochar also reduces the leaching of hydrocarbons in soils. Zand and Grathwohl (2016) confirmed that biochar is a rich sorbent and demonstrated that its particle size is inversely proportional to the hydrocarbon immobilization rate, with greater effectiveness when the powdered amendment is used. According to Sander and Pignatello, the sorption of hydrocarbons through the use of biochar is due to the presence of electron donor-acceptor interactions through π-π radicals on the surface of the amendment and the hydrocarbon; with biochar the donor and hydrocarbon the electron acceptor.…”
Section: Biochar In Soils Contaminated With Hydrocarbonsmentioning
confidence: 63%
“…Many of these reported positive correlations between dPyC with DOC and source PyC concentration (Bi et al, 2018;Güereña et al, 2015;Jones et al, 2019). In contrast, several studies reported a reduction in DOC export after biochar or charcoal amendment (e.g., Abdelrahman et al, 2018;Braun et al, 2020;Zand & Grathwohl, 2016), suggesting initial sorption of OM to the added PyC surface. Furthermore, many of these papers noted or measured variability in time post-fire or post-addition of charcoal as factors in leaching of PyC (e.g., Bi et al, 2018;Jones et al, 2019;Santos et al, 2017), highlighting the need for investigation on the controls on the timing of post-fire dPyC fluxes.…”
Section: 1029/2023gb008092mentioning
confidence: 99%